A Multisensory Deficit in the Perception of Pleasantness in Parkinson's Disease. - Utz, Kathrin; Martini, Max; Mrochen, Anne; Lambrecht, Vera; Süß, Patrick; Renner, Bertold; Freiherr, Jessica; Schenk, Thomas; Winkler, Jürgen; Marxreiter, Franz (Journal of Parkinson's Disease, 2021)
BACKGROUND: There is growing interest in non-motor symptoms in Parkinson's disease (PD), due to the impact on quality of life. Anhedonia, the inability to experience joy and lust, has a prevalence of up to 46% in PD. The perception of pleasantness of an odor is reduced in anhedonia without PD. We previously showed a reduced hedonic olfactory perception in PD, i.e., patients evaluated odors as less pleasant or unpleasant compared to controls. This deficit correlated with anhedonia. OBJECTIVE: We aimed to confirm these findings. Moreover, we hypothesized that the perception of pleasantness in PD is affected on a multisensory level and correlates with anhedonia. Therefore, we assessed olfactory, visual and acoustic evaluation of pleasantness in PD and healthy individuals. METHODS: Participants had to rate the pleasantness of 22 odors, pictures, and sounds on a nine-point Likert scale. Depression, anhedonia, and apathy were assessed by means of questionnaires. Results of the pleasantness-rating were compared between groups and correlated to scores of the questionnaires. RESULTS: In particular pleasant and unpleasant stimuli across all three modalities are perceived less intense in PD, suggesting that a reduced range of perception of pleasantness is a multisensory phenomenon. However, only a reduction of visual hedonic perception correlated with anhedonia in PD. A correlation of reduced perception of pleasantness with apathy or depression was not present. CONCLUSION: We provide evidence for a multisensory deficit in the perception of pleasantness. Further studies should delineate the underlying neural circuity and the diagnostic value to detect neuropsychiatric symptoms in PD.
EVALuna2:470167